2023
DOI: 10.3390/su15054689
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Arsenate from Contaminated Water via Combined Addition of Magnesium-Based and Calcium-Based Adsorbents

Abstract: The effects of the combined addition of Mg- and Ca-based adsorbents (MgO, Mg(OH)2, MgCO3, CaO, Ca(OH)2, and CaCO3) were systematically tested for improving arsenic-removal performance and inhibiting the leaching of base material components from the adsorbent. Arsenic-removal tests were conducted with each single type or combination of two types of adsorbents. Results obtained after the combined-addition tests were compared with those obtained from the single-addition test with each adsorbent. The arsenic-remov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…This is confirmed both by the elemental analysis presented in Table 2, where the Mg content decreases after As(III) adsorption, and by the appearance of the peak in the FTIR corresponding to the As-O-Mg vibrations (Figure 4). In recent studies [54,55], the presence of magnesium has been shown to have a significant effect on arsenic removal. The Mg 2+ ions contained in MgO, as demonstrated via EDS analysis and FTIR, are successfully deposited on the surface of the activated carbon and thus exhibit a corresponding affinity with As that enhances the adsorption effect of the modified activated carbon.…”
Section: Effect Of Modification Of Activated Carbonmentioning
confidence: 99%
See 1 more Smart Citation
“…This is confirmed both by the elemental analysis presented in Table 2, where the Mg content decreases after As(III) adsorption, and by the appearance of the peak in the FTIR corresponding to the As-O-Mg vibrations (Figure 4). In recent studies [54,55], the presence of magnesium has been shown to have a significant effect on arsenic removal. The Mg 2+ ions contained in MgO, as demonstrated via EDS analysis and FTIR, are successfully deposited on the surface of the activated carbon and thus exhibit a corresponding affinity with As that enhances the adsorption effect of the modified activated carbon.…”
Section: Effect Of Modification Of Activated Carbonmentioning
confidence: 99%
“…Moreover, activated carbon modified with MgSiO 3 (magnesium silicate) was applied to remove Pb(II) [53]. In recent studes [54,55], the presence of magnesium has shown a significant effect on arsenic removal. Mg 2+ ions exhibit a corresponding affinity with As that enhances the adsorption effect of the modified activated carbon.…”
Section: Introductionmentioning
confidence: 99%